2019
DOI: 10.1021/acsbiomaterials.9b00812
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole Nanocones and Dynamic Piezoelectric Stimulation-Induced Stem Cell Osteogenic Differentiation

Abstract: Imitating the physiological microenvironment of living cell and tissues opens new avenues of research into the application of electricity to medical therapies. In this study, dynamic piezoelectric stimulation is generated in a dynamic culture because of the piezoelectric effect of the poly(vinylidene fluoride)−polypyrrole (PVDF−PPy) electroactive composite. Combined with PPy nanocones, dynamic piezoelectric signals are effectively and continuously provided to cells. In the presence of dynamic piezoelectric sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…PPy nanocone geometry on a piezoelectric poly(vinylidene fluoride) (PVDF) membrane (PPy-PVDF NS) was compared to a PPy film on a PVDF membrane (PPy-PVDF IFS). 86 When mechanically stimulated via cyclic loading, BMSCs on PPy-PVDF NS membranes showed significantly higher levels of Runx2 and Col-1 compared to the PVDF-only condition. The authors hypothesize that one reason for the increased osteogenic potential of the PPy-PVDF NS materials compared to the PPy-PVDF IFS materials may be attributed to the nanocone structures providing more surface area for cell adhesion, which was supported by the observation of more elongated cell morphology on these scaffolds.…”
Section: In Vitro Characterization Of Cp-bmsmentioning
confidence: 92%
See 1 more Smart Citation
“…PPy nanocone geometry on a piezoelectric poly(vinylidene fluoride) (PVDF) membrane (PPy-PVDF NS) was compared to a PPy film on a PVDF membrane (PPy-PVDF IFS). 86 When mechanically stimulated via cyclic loading, BMSCs on PPy-PVDF NS membranes showed significantly higher levels of Runx2 and Col-1 compared to the PVDF-only condition. The authors hypothesize that one reason for the increased osteogenic potential of the PPy-PVDF NS materials compared to the PPy-PVDF IFS materials may be attributed to the nanocone structures providing more surface area for cell adhesion, which was supported by the observation of more elongated cell morphology on these scaffolds.…”
Section: In Vitro Characterization Of Cp-bmsmentioning
confidence: 92%
“…Varying geometries of conducting polymer substrates under various stimulation regimes have also been evaluated in vitro to further characterize material–electrical influences on BMSC differentiation. PPy nanocone geometry on a piezoelectric poly­(vinylidene fluoride) (PVDF) membrane (PPy-PVDF NS) was compared to a PPy film on a PVDF membrane (PPy-PVDF IFS) . When mechanically stimulated via cyclic loading, BMSCs on PPy-PVDF NS membranes showed significantly higher levels of Runx2 and Col-1 compared to the PVDF-only condition.…”
Section: In Vitro Characterization Of Cp-bmsmentioning
confidence: 99%
“…Besides the effect on neurite regulation, the FEMs‐mediated electrical stimulation on promoting osteogenic or myogenic differentiation of stem cells in the field of tissue engineering has drawn extensive attention as well. [ 37a,80 ]…”
Section: Fem‐based Biomedical Applicationsmentioning
confidence: 99%
“…Promising effects of electrical stimulation on cellular behavior motivate the employment of FEMs for various applications in tissue repair or stimulation for function recovery, particularly in bone defect repair, where electrical stimulation via FEMs has been shown to enhance bone regeneration; [ 88 ] in skeletal muscle regeneration, promote the myogenic formation and induce muscle extraction; [ 80c ] and in neural stimulation, promote neurite sprouting and activate neurite function (Figure 5c). [ 74b,77 ] These approaches have been well‐studied in recent years and there are already some excellent reviews on this topic for readers’ reference.…”
Section: Fem‐based Biomedical Applicationsmentioning
confidence: 99%
“…Moreover, CPs with nano morphology, which mimics the natural morphology of the extracellular matrix (ECM), can be easily fabricated via electrochemical and chemical polymerization on various substrates, and makes it an outstanding coating used in the biomedical field [9,10]. Actually, many studies confirmed that the PPy applied with electrical stimulation (ES) could promote the expression of proliferation and differentiation for tissue regeneration such as bone and nerves [11][12][13]. However, PPy does not display functional groups to help it adhere to surfaces [14]; therefore, generating composite materials with PPy and other adhesive polymers can effectively enhance the functionality of PPy-containing coatings.…”
Section: Introductionmentioning
confidence: 99%